Exploiting root microbiota for biological control of soil-borne Rhizoctonia solani - erdogmus, sumeyye (2020)
Rhizoctonia solani is a ubiquitous soil-borne necrotrophic plant pathogen causing pre- and postemergence damping-off, root rot and basal stem rot on oilseed rape and canola. Alternative methods to cultural or chemical control against this important pathogen have recently received more attention. The potential of soil microorganisms to control phytopathogens and stimulate plant growth is well known, however, the type of interactions between microbial communities and plants are not well understood. The growth and activity of soil-borne pathogens can be inhibited by specific microbes or microbial consortia. The aim of the studies described in this thesis was to get insight into the functional basis of interactions between the soilborne fungal pathogen Rhizoctonia solani AG2-1 and root-associated antagonistic bacteria in the rhizosphere of Brassica napus and A. thaliana. Firstly, in this study, candidate bacterial strains were identified for plant protection against R. solani AG2-1. Bacterial strains isolated from agricultural soils were screened in vitro for their ability to protect Arabidopsis thaliana against R. solani AG2-1 infection. To determine the effects of the fungal pathogen and bacteria on plant survival, plant counts of live or dead seedlings following inoculation with bacterial strains and AG2-1 were made daily for a period of 7 days in in vitro assays. The results showed that beneficial bacterial strains can protect plant survival of up to 80% against R. solani AG2-1 infection. Ten bacterial strains were selected based on their capacity to protect or infect A. thaliana and were included in further tests on their effect on B. napus in the presence or absence of the AG2-1 in media and in soil. In vitro results showed that although Pseudomonas (CL58) and Paeniobacillus (CL52) were pathogenic to A. thaliana, they did not infect B. napus. The selected bacterial strains were able to suppress disease development on B. napus and were antagonistic against R. solani AG2-1. Pseudomonas (CL58), which was pathogenic on A. thaliana, was most effective in inhibiting fungal growth in vitro. However, the effect of bacterial strains in soil was less consistent showing the lowest disease on hypocotyl and taproot observed in interactions with Paeniobacillus (CL58) and Paenarthrobacter (MF26). Bacterial strains and AG2-1 were able to alter the ionome of B. napus, and A. thaliana. While more ions accumulated in B. napus plants not inoculated with R. solani, the ionome changes differed to those observed in A. thaliana. In A. thaliana, inoculations with Mycobacterium (MF88), Pedobacter (176) and Paeniobacillus (CL52) resulted in increased abundance of Manganese (Mn+ ), Calcium (Ca+ ) and phosphorus (P+ ), respectively under fungal inoculation compared to the not-inoculated control. Phosphorus as one of the most important mineral nutrients to promote plant growth was also increased in B. napus, under fungal inoculation by three bacterial strains-Paeniobacillus (CL52), Mycobacterium (MF88) and Arthrobacter (145). Moreover, these three bacterial strains also decreased Na+ in the absence of the pathogen. The accumulation Na+ in the plant tissues inhibits photosynthesis thus these three bacterial strains can benefit plant growth by reducing Na+ and increasing P+ . My results thus support the view that microbial communities can be potentially utilized for plant-growth promotion and inhibition of AG2-1. However further research is needed on how best to increase their effectiveness in soil. Future studies will investigate the chemical and molecular mechanisms of plant protection by bacterial strains against R. solani for future improvement of biological control.